2021
DOI: 10.3390/ph14020158
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Bioevaluation of Novel 99mTc-Labeled Complexes with a 2-Nitroimidazole HYNIC Derivative for Imaging Tumor Hypoxia

Abstract: To develop novel 99mTc-labeled single-photon emission computed tomography (SPECT) radiotracers for imaging hypoxia, a novel HYNICNM ligand (6-hydrazinonicotinamide (HYNIC) 2-nitroimidazole derivative) was designed and synthesized. It was radiolabeled with technetium-99m using tricine/trisodium triphenylphosphine-3,3′,3′′-trisulfonate (TPPTS), tricine/sodium triphenylphosphine-3-monosulfonate (TPPMS) and tricine as co-ligands to obtain [99mTc]Tc-tricine-TPPTS-HYNICNM, [99mTc]Tc-tricine-TPPMS-HYNICNM, and [99mTc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The linker, which connects the targeting group with the chelating group, plays an important role in adjusting the affinity of tracers and their biodistribution properties in organisms. Using amino acids as linkers could improve the hydrophilicity and alter the metabolism of radioactive drugs; thus, this approach may reduce the uptake of the tracer by nontarget organs such as the kidney and improve the uptake of radiotracers in tumors. , Therefore, in this work, hydrophilic d -proline was selected as a linker to connect the hydrazinonicotinamide (HYNIC) group and FAPI moiety, and tricine and 3,3′,3″-phosphanetriyltris trisodium salt (TPPTS) were used as co-ligands to form a technetium complex , to obtain a potential tumor imaging agent targeting FAP.…”
Section: Introductionmentioning
confidence: 99%
“…The linker, which connects the targeting group with the chelating group, plays an important role in adjusting the affinity of tracers and their biodistribution properties in organisms. Using amino acids as linkers could improve the hydrophilicity and alter the metabolism of radioactive drugs; thus, this approach may reduce the uptake of the tracer by nontarget organs such as the kidney and improve the uptake of radiotracers in tumors. , Therefore, in this work, hydrophilic d -proline was selected as a linker to connect the hydrazinonicotinamide (HYNIC) group and FAPI moiety, and tricine and 3,3′,3″-phosphanetriyltris trisodium salt (TPPTS) were used as co-ligands to form a technetium complex , to obtain a potential tumor imaging agent targeting FAP.…”
Section: Introductionmentioning
confidence: 99%
“…Scintigraphy imaging studies in mice bearing S180 tumors also showed a h accumulation of [ 99m Tc]46 in tumors with a tumor/normal tissue ratio of 3.39 ± 0.38, wh were in accordance with the biodistribution studies of [ 99m Tc]46. 50) were developed by Zhang and co-workers (Figure 23) [150]. In vitro stud showed that the three 99m Tc-labeled complexes remained stable in saline and in mou serum, and all were hydrophilic.…”
Section: Pharmaceutics 2023 15 X For Peer Review 15 Omentioning
confidence: 99%
“…The synthesis of compound 1 (HYNIC active ester) has been previously reported. 23 Compound 2 (HY-NICNF) was synthesized according to the reported literature, 22 and the reaction route is shown in Scheme 1. The general procedure for the preparation of HYNIC norfloxacin was as follows.…”
Section: T H Imentioning
confidence: 99%